2017
DOI: 10.1080/0167482x.2017.1308349
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in reproductive medicine: the motivations of infertile women to participate in a randomised controlled trial

Abstract: The decision to participate in an RCT was an informed one. Infertile women in a stressful treatment situation participated in an RCT in the hope of finding a therapy to improve IVF outcomes for themselves and for other infertile women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Two trials (Smith et al, 2006(Smith et al, , 2018 undertaken by three authors (CS, RN, NJ) of this review were independently assessed by authors MA, AT and ZS. The quality of the acupuncture delivered during the trial was assessed by two authors using the NICMAN scale (Smith et al, 2017). The NICMAN scale comprises 11 domains related to study design, rationale of the intervention, specific criteria relating to the acupuncture characteristics including needling stimulation, whether manually or using electro-stimulation, duration and frequency of treatment and practitioner training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two trials (Smith et al, 2006(Smith et al, , 2018 undertaken by three authors (CS, RN, NJ) of this review were independently assessed by authors MA, AT and ZS. The quality of the acupuncture delivered during the trial was assessed by two authors using the NICMAN scale (Smith et al, 2017). The NICMAN scale comprises 11 domains related to study design, rationale of the intervention, specific criteria relating to the acupuncture characteristics including needling stimulation, whether manually or using electro-stimulation, duration and frequency of treatment and practitioner training.…”
Section: Methodsmentioning
confidence: 99%
“…Women seek information and treatment about complementary health approaches to increase their chances of achieving a pregnancy and live birth (de Lacey et al, 2017;Rayner et al, 2009Rayner et al, , 2011, and also to improve their health, quality of life and to reduce stress whilst undergoing treatment cycles (de Lacey and Smith, 2013). Acupuncture has become a frequently used adjunctive treatment prior to and during IVF treatment (Domar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Participants described themselves as active agents and their motivations as searching for a better outcome for their infertility ( de Lacey et al, 2017 ); however, they were largely uncertain as to whether acupuncture would impact the medical outcome of pregnancy and live birth for them. Indeed, we recently reported that the findings of the RCT showed no difference in the primary outcome of live birth and pregnancy outcomes between groups ( Smith et al, 2018 , Smith et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that female participants in the qualitative study were proactive in seeking a better treatment outcome through involvement in the RCT, and described a sense of regained control over their situation ( de Lacey et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, when informed IVF is in need, infertile women are stressful and hoping to find a therapy to improve IVF outcomes for themselves and for other infertile women, [ 29 ] under this circumstance, acupuncture is widely used by individuals undergoing IVF [ 30 , 31 ] ; it is reported to ameliorate stressful emotions during IVF procedures, [ 13 , 32 , 33 ] reduce pain intensity and analgesic consumption, [ 15 ] modulate neuroendocrine factors and immune factors, increase blood flow to the uterus and ovaries, [ 34 ] promote the absorption of endometrial cavity fluid, and improve the uterine environment and endometrial receptivity. [ 35 ] Meanwhile, when applied around the time of embryo transfer, acupuncture may be effective when compared with no adjunctive treatment with increased clinical pregnancies.…”
Section: Discussionmentioning
confidence: 99%